The Effect of Debt to Equity Ratio, Return on Equity, and Return on Investment on Share Price at PT Alam Sutera Realty, Tbk - Abriyanni Abriyanni; Nurul Huda (INVOICE : JURNAL ILMU AKUNTANSI, 2023)
This study aims to investigate the impact of the Debt to Equity Ratio, Return on Equity, and Return on Investment on stock prices. The research employs financial statement data from PT Alam Sutera Realty, Tbk for a span of 12 years, ranging from 2010 to 2021. The study adopts the purposive sampling method for sample selection. The data undergoes analysis utilizing SPSS, encompassing classical assumption tests, including the autocorrelation test, normality test, multicollinearity test, and heteroscedasticity test, followed by multiple linear regression, multiple correlation coefficients, coefficient of determination, T-test, and F-test. The hypothesis testing is conducted with a significance level set at 5%. The findings of this study indicate that the Debt to Equity Ratio variable exerts a significant influence on stock prices, thereby affecting the financial performance of PT Alam Sutera Realty, Tbk. Similarly, the Return on Equity variable is shown to have a significant impact on stock prices, underscoring its importance in determining the company's stock valuation. However, it is noteworthy that the Return on Investment variable does not exhibit a significant effect on stock prices in this context, suggesting that other factors may play a more prominent role in influencing stock prices within the chosen time frame. In conclusion, this research provides valuable insights into the relationship between financial indicators and stock prices, shedding light on the specific impact of Debt to Equity Ratio and Return on Equity. These findings can serve as a foundation for further financial analysis and investment decisions in the context of PT Alam Sutera Realty, Tbk.